The need and possibility for evangelizing through the internet - Časni, Danijel (Array, 2019)
In today’s society of technological advancement, evangelizing through the Internet is an adequate tool for proclaiming the Good News. By using the Internet, the Church communicates on a local level to its local church but also on a broader scale at the global level, thus fulfilling its mission of proclaiming the Gospel “to all the nations.” The paper talks about the need of using the Internet and social networks for evangelism, as a medium for communicating the message of salvation and hope in Jesus Christ. By analyzing the usage of the Internet in Evangelical churches in Croatia we gain an insight into the current condition and the possibility of a more efficient way of using the new media in proclaiming the Good News.